2022
DOI: 10.1136/jnnp-2022-329713
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of disability in paediatric multiple sclerosis: evidence from a multi-national registry

Abstract: BackgroundEarly recognition of markers of faster disability worsening in paediatric-onset multiple sclerosis (MS) is a key requisite of personalised therapy for children with MS at the earliest possible time.ObjectiveTo identify early predictors of rapid disability accrual in patients with paediatric-onset MS.MethodsUsing the global MSBase registry, we identified patients who were <18 years old at the onset of MS symptoms. The clinico-demographic characteristics examined as predictors of future MS Severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the last years, improved therapeutic management and particularly greater use of highly active therapies has helped improve the short-term prognosis of patients with PoMS. 14,15 Particularly, several studies clearly demonstrated high effectiveness of RTX/OCR in PoMS. 36,16 These studies of the evolution of disease in patients receiving RTX/OCR with maintenance therapy every 6 months demonstrated a marked reduction in disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, improved therapeutic management and particularly greater use of highly active therapies has helped improve the short-term prognosis of patients with PoMS. 14,15 Particularly, several studies clearly demonstrated high effectiveness of RTX/OCR in PoMS. 36,16 These studies of the evolution of disease in patients receiving RTX/OCR with maintenance therapy every 6 months demonstrated a marked reduction in disease activity.…”
Section: Discussionmentioning
confidence: 99%